Sikhism : An attempt at Religious Synthesis and Unity - Singh, Dharam (Journal of Dharma, 1987)
Some thoughtful observers have been pointing out for quite some time now that mankind is in the throes of a severe crisis. The expressions used to characterize the twentieth century convey, one way or the other, signifi- cant aspects of man’s predicament. Our age has been variously described as an "age of anxiety," and "age of revolt" and an .. age of unreason." In .. spite of all the advances made by science and technology, there seems to be something wrong with human affairs. The words of St. Paul that "there is fighting without and fear within" describe the stark reality of the situation today. Religion seems to be the only remedica! force to eradicate this ’fear within’ and the ’fighting without’ and to enable man to enjoy ’the promised land.’ Religion is 110t a formal and’ aimless system of arid beliefs and mechanical rituals. Nor is it the ’opium of the people’ as Karl Marx and his followers would have us believe, something not only incapable of bringing about social justice but actually antagonistic to it. It does not end, as it appears to many, with cultivating mystical experiences and practising a few mysterious rites connected with birth, marriage and death. Religion has, as amply evidenced by archaeology and history. played an important part in all the civilizations known to man, and it is bound to play a crucial role in the present day world as well. While conceding the universal significance of religion, we should concede the widespread ignorance of it as well. Not much effort seems to have been made to findout what really constitutes religion because this task has till recently remained in the bands of priests and was never considered in academic discipline. It has generally been looked upon as reactionary basically, and opposed to all change and progress. This concept has generally been used in a somewhat loose and subjective manner and, what is more important, in the ways that best served the interests of their authors.